Performance of Turkeys Under Extensive and Semi - intensive Systems of Management in Khartoum State (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was carried out to determine and compare theperformance traits of turkeys under semi-intensive and extensive systemsof management in Khartoum State, Sudan. A commercial breed of turkey(BUT Big 6) was used. Birds were kept in an open-sided, deep litterpoultry house (semi intensive system) and fenced enclosures (extensivesystem) from week 17 to weeks 24 and 28 and fed on turkey finisher andsupplement diets, respectively. Parameters assessed were feed intake,body weight, body weight gain, feed conversion ratio (for each feed),mortality and cost and profit. Results of feed intake indicated a consistentincrease with increase in age in both systems of management up to week22 followed by a consistent decrease in feed intake up to the end of theexperiment at week 28. Body weight increased with increase in age inboth systems of management up to week 24 followed by a slight increaseup to week 28. Turkeys kept under semi-intensive system of managementconsumed higher amounts of feed, gave heavier finishing weight, averageweight gain, heavier carcass weight and higher profit than those keptunder extensive system up to week 24 and lower mortality percentage andprofit from week 25 to week 28. No difference between treatments wasfound in dressing percentage and wholesale cuts. The study concludedthat the semi- intensive system is better for turkey production up to week24.
Keywords: Turkey; BUT Big 6; semi-intensive system; extensive system; performance; Sudan